Ancient Indian Cosmological Concepts During Vedic and Puranic Era: A Literature Survey (Prakriti - The International Multidisciplinary Research Journal, 2024)
Ancient Indian cosmological concepts from the Vedic and Puranic eras reveal profound insights  into the universe's nature and origins. Swami Vivekananda emphasized the importance of  understanding the past to shape the future, underscoring the need for a comprehensive analysis of  Vedic literature. This survey explores various facets, including ancient Indian astronomy, the  significance of celestial entities, and creation theories in key texts like the Vedas and Puranas. By  examining these concepts, we can appreciate the interconnectedness of geography, mythology, and  spirituality in ancient India.
Keywords: cosmological; Puranic; employs; historical